MicroRNAs secreted by the parasitic nematode Brugia malayi disrupt lymphatic endothelial cell integrity. - Hailey Johnson; Stephanie Banakis; Matthew Chung; Elodie Ghedin; Denis Voronin (PLoS Neglected Tropical Diseases)
Lymphatic filariasis (LF) is a neglected tropical disease affecting over 51 million people in 72 endemic countries. Causative agents of LF are mosquito-borne parasitic nematodes Wuchereria bancrofti, Brugia malayi, and Brugia timori. The adult parasites impact the integrity of lymphatic vessels and damage valves, leading to a remodeling of the lymphatic system and lymphatic dilation. Chronic infections can develop into severe clinical manifestations, primarily lymphedema, hydrocoele, and elephantiasis. Mechanistic studies on the underlying pathology due to the parasite are necessary to better manage human filariasis. Since parasite molecules, such as microRNAs (miRNAs), can be found in secreted extracellular vesicles (EVs) and are transported between parasite and host cells, we hypothesized that these could also play a role in the development of pathology in LF. In this study, we tested two B. malayi miRNAs previously detected in vitro in the culture media of microfilarial stages of worms. While one is Brugia-specific (bma-miR-5864) and the other nematode-specific (bma-miR-86), both miRNAs are secreted in high abundance. We first examined the in vitro response by transcriptomic profiling of human lymphatic endothelial cells to treatment with these miRNAs, which allowed us to identify genes involved in maintaining the integrity of the lymphatic endothelium. We then measured the effect of these miRNAs on the regulation of proteins necessary for cell integrity, demonstrating downregulation leading to a significant increase in the permeability of the endothelium monolayer. With this study we identify parasite miRNAs involved in undermining the integrity of endothelial cells, thus potentially contributing to the development of pathology. These findings could pave the way for a novel treatment strategy where the inhibition of parasite-secreted molecules could slow the progression of LF pathology. From a broader perspective, the miRNAs secreted by filarial parasites could potentially be used in the future for diagnosing and monitoring disease progression or treatment efficacy.